Breeding and Health Benefits of Fruit and Nut Crops 2018
DOI: 10.5772/intechopen.74977
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Breeding of Persimmon

Abstract: The genus Diospyros, which is distributed in tropical and subtropical regions of the world, contains hundreds of plant species. However, four species of them have commercial importance. D. kaki Thunb. is the most widely cultivated species of the Diospyros genus. Persimmon (D. kaki Thunb.) is grown in many parts of the world that display subtropical climate conditions. In recent years, the cultivation of persimmon has found renewed interest in various countries of the Mediterranean basin. In China (which is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…D. kaki is the most economically important and widely cultivated species in the world. Cultivars of D. kaki are grown in Australia, Brazil, China, Iran, Israel, Italy, Japan, New Zealand, and United States of America [7,8]. The geographical origin of the D. kaki species is not yet known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…D. kaki is the most economically important and widely cultivated species in the world. Cultivars of D. kaki are grown in Australia, Brazil, China, Iran, Israel, Italy, Japan, New Zealand, and United States of America [7,8]. The geographical origin of the D. kaki species is not yet known.…”
Section: Introductionmentioning
confidence: 99%
“…Previous phylogenetic studies revealed that two species distributed in Asia, Diospyros glandulosa (2n=2x=30) and Diospyros oleifera (2n=2x=30), are most likely ancestors of D. kaki (2n= 6x= 90) [2,7,8]. Their phylogenies also suggested that D. kaki originated in Asia through polyploidization.…”
Section: Introductionmentioning
confidence: 99%
“…The genus persimmon Diospyros ( Ebenaceae ) comprises more than 400 evergreen and deciduous tree species that are distributed worldwide [ 1 ]. Among these species.…”
Section: Introductionmentioning
confidence: 99%
“…Persimmon was introduced into North America in the mid-1800s and later into Australia and New Zealand. In South America, persimmon cultivation started in the late 19th century (Kluge & Tessmer, 2018;Yesiloglu et al, 2018).…”
Section: I1 Origin Botany and Morphology Of Persimmonmentioning
confidence: 99%
“…In Italy, almost 90% of persimmon production is based on 'Kaki Tipo'. In Israel, 'Triumph', under the 'Sharon' trademark, is the main cultivar and consists of 95% of total persimmon production (Yesiloglu et al, 2018). In the last 20 years, Spain's persimmon cultivation grown the most and more quickly in this area, mainly due to the increased production of cultivar Rojo Brillante in the Valencian Community of Spain .…”
Section: Introductionmentioning
confidence: 99%